2015
DOI: 10.1002/jsfa.7279
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐chemical properties and fatty acid composition of pomegranate, cherry and pumpkin seed oils

Abstract: Pomegranate, cherry and pumpkin seed oils can be an excellent source of bioactive molecules and antioxidant compounds such as polyphenols, carotenoids and unsaturated fatty acids. These seed oils can be included both as preservatives and functional ingredients in the food, pharmaceutical and cosmetic fields and can contribute to disease prevention and health promotion. Moreover, high absorbance of UV light indicates a potential use of these oils as filters from radiations in the food, pharmaceutical, and cosme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 36 publications
3
57
3
Order By: Relevance
“…10 In addition, PSO contains carotenoids, in high concentration, and sterols as stigmastatrienol, stigmastadienol, and spinasterol. 10,11 Reports have shown the therapeutic effects of PSO, primarily highlighting the antidiabetic, antibacterial, anti-oxidant and anti-inflammatory properties of the edible oil with the highest contribution to the anti-oxidant capability being related to the polar fraction of the oil, mainly tocopherols. [12][13][14][15] The mechanism underlying the anti-oxidant activity involves the blockage of 5-alpha reductase enzyme action.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, PSO contains carotenoids, in high concentration, and sterols as stigmastatrienol, stigmastadienol, and spinasterol. 10,11 Reports have shown the therapeutic effects of PSO, primarily highlighting the antidiabetic, antibacterial, anti-oxidant and anti-inflammatory properties of the edible oil with the highest contribution to the anti-oxidant capability being related to the polar fraction of the oil, mainly tocopherols. [12][13][14][15] The mechanism underlying the anti-oxidant activity involves the blockage of 5-alpha reductase enzyme action.…”
Section: Introductionmentioning
confidence: 99%
“…Oleic acid and linoleic acid were found to be major fatty acids with a ratio of 36.73% and 39.45 %, respectively. Bernardo-Gil et al 2001; Siano et al (2016) reported similar results. Doğantürk and Seçilmiş Canbay (2019) reported that oleic acid was in the range of 42.625 to 55.265 g/100 g and linoleic acid with 23.276 g/100 g. The oleic acid value was higher than our study.…”
Section: Physicochemical Analysismentioning
confidence: 65%
“…Some edible oils such as cold-pressed and virgin oils can be directly consumed. In addition to seed oils such as soy, sunflower, cotton and canola, palm and olive oil are among the most commonly used fruit oils (Siano et al, 2016). The need for alternative vegetable oil sources is increasing day by day.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the chemical composition of PSO in terms of fatty acid composition exhibited that PSO contained 40.58% oleic acid, 27.06% stearic acid, 17.39% palmitic acid and 14.97% linoleic acid. Siano et al (2016) have noted that the polyunsaturated FA (PUFA), monounsaturated FA (MUFA) and saturated FA (SFA) contents in PSO cultivated in southern Italy were of 48.14%, 25.54%, and 25.20%, respectively. The high degree of unsaturated FA makes PSO suitable to be used as valuable drying agent, while low value of free FA contents indicates the suitability of PSO as edible oils.…”
Section: Chemical Characterization Of Pumpkin Seed Oilmentioning
confidence: 99%